?PREPARATION AND EVALUATION OF ALKYD RESIN FROM CASTOR OIL ? Short Communication - gunniyi, D S O; Njikang, G N (Biological Sciences - PJSIR, 2000)
Alkyd resin is known for its good drying performances and good resistance to weathering and has almost replaced drying oils as binders for gloss finishes, varnishes, wood primers, enamels and lacquers.